1993
DOI: 10.1007/bf00004567
|View full text |Cite
|
Sign up to set email alerts
|

β-adrenergic signal transduction in fish: interactive effects of catecholamines and cortisol

Abstract: The elevation of plasma catecholamine levels during acute stress initiates a series of compensatory physiological and biochemical mechanisms to alleviate the disruptive effects of stress on blood oxygen transport. Of particular importance is the β-adrenergic activation of a Na(+)/H(+) antiporter associated with the red blood cell (rbc) membrane. Upon activation, the Na(+)/H(+) antiporter extrudes H(+) from the rbc and the resultant alkalinization of the rbc interior serves to enhance both the affinity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 50 publications
1
17
1
1
Order By: Relevance
“…Trout red blood cell β‐ARs control the activity of a Na/H + exchanger (βNHE) located in the red cell plasma membrane. Stimulation of red blood cell β‐ARs leads to βNHE activation that ultimately results in an increased hemoglobin/oxygen binding affinity during times of stress [18]. Our results do not concur with previous pharmacological studies [39], suggesting that a β 2 ‐AR subtype controls the activity of the trout red blood cell βNHE.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Trout red blood cell β‐ARs control the activity of a Na/H + exchanger (βNHE) located in the red cell plasma membrane. Stimulation of red blood cell β‐ARs leads to βNHE activation that ultimately results in an increased hemoglobin/oxygen binding affinity during times of stress [18]. Our results do not concur with previous pharmacological studies [39], suggesting that a β 2 ‐AR subtype controls the activity of the trout red blood cell βNHE.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, fish β‐ARs elicit responses unique to particular species or groups of fish. For example, catecholamine release causes an increase in hemoglobin/oxygen binding affinity in the rainbow trout erythrocyte by activation of a red blood cell β‐AR [18].…”
mentioning
confidence: 99%
“…The hypothalamus-pituitary-interrenal activity was triggered by stressor, which resulting in cortisol secretion (Perry & Reid, 1993) and increased the blood glucose (Tomasso et al, 1980). In this study, low water temperature as a stressor tend to increase the stress of grey mullets.…”
Section: Component Experimentsmentioning
confidence: 57%
“…Furthermore, when blood from cortisol-treated fish was exposed to hypoxia in vitro, an increase in the number of 0B-adrenoceptors on the rbc surface occurred, presumably, as receptors were mobilized from the internal pool. Additionally, the results of several previous studies (Martilla and Nikinmaa 1988;Reid et al 1993) have demonstrated an increase in the number of cell surface receptors in response to hypoxia, in vitro, in the absence of elevated cortisol levels (see review by Perry and Reid 1993). A similar hypoxia protocol using uncannulated fish demonstrated that plasma cortisol levels (ranging between 15-50 ng ml-') were not different, compared with normoxic fish, during 48h of hypoxia at a PwO 2 of 8.0 kPa (unpublished observations).…”
Section: Discussionmentioning
confidence: 97%